Webb's physics of medical imaging - Flower, M. A. [ (Maggie A.)]; Webb, Steve , 1948- (Series in medical engineering and biomedical engineering, 2012)
"This updated text explains the physical principles governing medical imaging. It places different techniques in context with each other to provide historical perspective and insight on future developments. It also illustrates techniques through examples of clinical imaging applications. The book covers the use of x-rays in diagnostic radiology and computed tomography in radiotherapy planning. It also discusses the tools and techniques of radioisotope, ultrasound, magnetic resonance, infrared, and optical imaging, along with the mathematics involved in image formation and processing, image interpretation, and computational requirements of imaging systems" --Provided by publisher